Biosurfactant-Assisted Hydrogen Evolution: Effects of Sapindus Rarak Extract on Alkaline Electrolysis Performance - Santoso, Mardi; Sinurat, David Fernando; Ahmad, Anton Royanto; Hamidi, Nurkholis; Purnami, Purnami (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2026)
Hydrogen production through alkaline water electrolysis is a promising pathway for clean energy generation, yet its efficiency is often limited by gas bubble accumulation on electrode surfaces. This study explores the use of a natural surfactant derived from Sapindus rarak (lerak) as a green additive to improve hydrogen evolution reaction (HER) performance. Experimental results show that the natural surfactant-enhanced system achieved a 135% increase in cumulative hydrogen yield over 10 minutes. Mechanistically, the natural surfactant lowered the surface tension, reduced bubble nucleation size, and promoted faster detachment from the electrode surface, thereby preserving catalytic activity. Compared to synthetic surfactants like sodium lauryl sulfate, Sapindus rarak offers advantages in natural degradability, environmental safety, and regional availability. This study demonstrates that natural plant-based surfactants can serve as effective, eco-friendly enhancers in electrochemical hydrogen production. The results provide a foundation for integrating natural surfactants into scalable and sustainable green hydrogen systems.